2021
DOI: 10.1038/s41598-020-79684-2
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of arginine and fluoride on the growth of Lactobacillus rhamnosus GG

Abstract: The objectives of the in vitro study were: (1) to investigate the effect of combining L-arginine (Arg) and NaF on the growth of Lactobacillus rhamnosus GG (LRG); and (2) to identify an optimum synergistic concentration for the synbiotic (Arg + LRG)-fluoride (SF) therapy. 1% Arg + 2000-ppm NaF (A-SF) and 2% Arg + 2000-ppm NaF (B-SF) demonstrated antagonism against LRG (FIC > 4.0). Both XTT (2,3-bis-(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide) and WST-8 (2-(2-methoxy-4-nitrophenyl)-3-(4-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
0
3
0
1
Order By: Relevance
“…The pH estimation was done using a combination double-junction gel filled electrode (Oakton-Cole Palmer, Thermo Fisher Scientific, Loughborough, UK) attached to a potentiometer (Eutech™ 2700 pH meter, Thermo Fisher Scientific) as per previous studies 25,30) . The pH electrode was calibrated against external pH standards -pH: 4.01, 7.0, and 10.01 on each occasion when pH was duly estimated.…”
Section: Ph Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH estimation was done using a combination double-junction gel filled electrode (Oakton-Cole Palmer, Thermo Fisher Scientific, Loughborough, UK) attached to a potentiometer (Eutech™ 2700 pH meter, Thermo Fisher Scientific) as per previous studies 25,30) . The pH electrode was calibrated against external pH standards -pH: 4.01, 7.0, and 10.01 on each occasion when pH was duly estimated.…”
Section: Ph Estimationmentioning
confidence: 99%
“…As per previous studies 23,25,30) , the F analysis was performed using F-ion selective electrode (F-ISE; Orion™ Fluoride Electrodes, Thermo Fisher Scientific) attached to an ion benchtop meter (Eutech™ 2,700 pH meter, Thermo Fisher Scientific). For F-ISE calibration, the prepared external standards were subjected to mV potential determination with the ion meter.…”
Section: F Analysismentioning
confidence: 99%
“…Mohammed et al [36] found that L-arginine can promote the growth of Lactobacillus rhamnosus GG (LrG), and 2% L-arginine and LrG syngenics can jointly inhibit the growth of Streptococcus mutans, which has the potential to become antibacterial agents. The latest study by Mohammed et al [37] found that L-arginine (1% / 2%) combined with NaF Volume 4 Issue 6 2022 Issue 7 2022…”
Section: Synbioticsmentioning
confidence: 99%
“…Недавние исследования показывают влияние комбинаций L-аргинина и фторида на рост Lactobacillus rhamnosus. Аргинин в зависимости от концентраций может увеличивать и задерживать пленкообразование, 2%-е содержание аминокислоты в среде обеспечивает оптимальный синбиотико-фторидный синергизм [16].…”
Section: рис 1 динамика изучения микроорганизмов в составе биопленок ...unclassified